2014
DOI: 10.1021/jp4107712
|View full text |Cite
|
Sign up to set email alerts
|

Crowding by Anionic Nanoparticles Causes DNA Double-Strand Instability and Compaction

Abstract: Up to the present, DNA structural transitions caused by cationic polymers as well as in concentrated solutions of neutral polymers are well documented, while a little is known about DNA interaction with like-charge species. Herein, changes in the structure of DNA induced by anionic nanoparticles of different sizes (20-130 nm) were investigated by combining single-molecule DNA fluorescent microscopy, to monitor the conformational dynamics of long-chain DNA, with spectroscopic methods, to gain insight into chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 28 publications
6
58
0
Order By: Relevance
“…It is seen in this figure that, at 1% BSA and 150 mM NaCl, the 166 kbp bacteriophage T4 DNA exhibits an elongated coil conformation, which is approximately 5 µm long (figure 4(A)), while at 15% BSA the DNA is tightly between these macromolecules and leads eventually to re-mixing. Note that it was still more recently shown that a few percents of negatively charged silica nanoparticles with diameters ranging from 20 to 135 nm are also able to trigger compaction of DNA from coil to globule configurations [45].…”
Section: Segregative Phase Separationmentioning
confidence: 99%
“…It is seen in this figure that, at 1% BSA and 150 mM NaCl, the 166 kbp bacteriophage T4 DNA exhibits an elongated coil conformation, which is approximately 5 µm long (figure 4(A)), while at 15% BSA the DNA is tightly between these macromolecules and leads eventually to re-mixing. Note that it was still more recently shown that a few percents of negatively charged silica nanoparticles with diameters ranging from 20 to 135 nm are also able to trigger compaction of DNA from coil to globule configurations [45].…”
Section: Segregative Phase Separationmentioning
confidence: 99%
“…Moreover, mechanically compacted DNA has recently been used as nanostructure template4 and also applied as protection against chemical, biochemical and mechanical stresses5. Learning from the nature, researchers have started applying the compaction tricks using polyamines67, surfactants89, liposomes10, nanoparticles1112, polymer13, osmoticants like polyethylene glycol (PEG)14, dendrimers1516, multivalent ions17, metal complex18, cyclodextrin19, peptides20 and proteins21 for compaction and storage of DNA for prolonged duration. Among these compacting agents, most important naturally occurring DNA compaction agents are proteins and polyamines like of spermine and spermidine etc2021.…”
mentioning
confidence: 99%
“…In contrast to the destabilization of DNA secondary structure observed by Zinchenko et al [29], Liu et al reported a significant increase of DNA melting temperature in solutions containing high concentrations of polyanion. At a similar ionic strength (2.5 mM Na + ) they measured an increase in the melting temperature of 12 bp DNA from 38°C to 50°C by just adding 1% PAANa to solution.…”
Section: Depletion and Compaction Of Dna In Solutions Caused By Negatmentioning
confidence: 74%
“…2 top) [29]. To avoid aggregation of nanoparticles, the experiments were performed at low salt concentrations (1 mM NaCl).…”
Section: Depletion and Compaction Of Dna In Solutions Caused By Negatmentioning
confidence: 99%
See 1 more Smart Citation